2015
DOI: 10.1088/0965-0393/23/2/025005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative tracking of grain structure evolution in a nanocrystalline metal during cyclic loading

Abstract: Molecular dynamics simulations were used to quantify mechanically-induced structural evolution in nanocrystalline Al with an average grain size of 5 nm. A polycrystalline sample was cyclically strained at different temperatures, while a recently developed grain tracking algorithm was used to measure the relative contributions of novel deformation mechanisms such as grain rotation and grain sliding. Sample texture and grain size were also tracked during cycling, to show how nanocrystalline plasticity rearranges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 74 publications
5
36
0
Order By: Relevance
“…However, in a nanocrystalline metal, it has been hypothesized that even modest plastic deformation can alter boundary character rather dramatically. For example, Panzarino et al showed that even small cyclic strains can cause nanocrystalline grains to rotate relative to their neighbors and create new twin boundaries [15]. Other proposed nanocrystalline deformation mechanisms could be associated with even more dramatic changes to the boundary network.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a nanocrystalline metal, it has been hypothesized that even modest plastic deformation can alter boundary character rather dramatically. For example, Panzarino et al showed that even small cyclic strains can cause nanocrystalline grains to rotate relative to their neighbors and create new twin boundaries [15]. Other proposed nanocrystalline deformation mechanisms could be associated with even more dramatic changes to the boundary network.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nanocrystalline metals have been reported to coarsen through stress-driven grain boundary migration [31,48,49], with such migration usually resulting in discontinuous grain growth [29]. Recent molecular dynamics simulations by Panzarino et al [50] also verify that grain rotation and coalescence can contribute to discontinuous grain growth during cyclic loading and that the magnitude of such coarsening increases with increasing number of applied loading cycles. Experimental observation of grain growth and its dependence on shear stress was also reported by Rupert et al [31], with higher stresses leading to more evolution.…”
Section: Subsurface Evolution In D = 3 Nm Samplementioning
confidence: 99%
“…However, grain growth can be accompanied by relaxation of nonequilibrium grain boundary structure, which significantly increases hardness [43]. Panzarino et al [50] also showed that strengthening can occur during cyclic deformation as a result of the formation of lower energy boundary configurations. For the gradient nanograined structure, only the coarsened grains near the surface have boundaries with relaxed structure, while the grains below remain close to the as-deposited state.…”
Section: Analysis Of the 250 Cycle Sample Inmentioning
confidence: 99%
“…Recently, Panzarino et al [6] characterized the grain structure evolution during the cyclic deformation of polycrystalline Al having grain size of 5 nm for 10 cycles. The cyclic strengthening was associated with the grain rotation, grain growth and the formation of many twin boundaries [6]. Like polycrystalline Al and Ni, MD simulations on the polycrystalline Cu with 5.5 nm grain size revealed the occurrence of grain coarsening during the cyclic deformation [7].…”
Section: Introductionmentioning
confidence: 99%